Analisis Faktor - Faktor Yang Memengaruhi Pengangguran Usia Muda Di Pulau Jawa - Cynthia, Dian Ayu; Hanifa, Nurul (Independent: Journal of Economics, 2024)
Youth unemployment is currently being experienced by many countries, including Indonesia. There are several factors that can influence youth unemployment in Indonesia. This research identifies several factors that influence youth unemployment on the island of Java in 2016 - 2022. Some of these factors include population size, provincial minimum wage (UMP), education level as measured by average years of schooling, and Labor Force Participation Rate (LFPR). The method used in this research is panel data regression using the Fixed Effect Model (FEM) from Stata 13. The results of this research show that population has a positive but not significant effect, and the provincial minimum wage and labor force participation variables have a positive and significant effect. significant. Meanwhile, the level of education has a negative and significant effect.